On the kinetic mechanism of dimethylarginine dimethylaminohydrolase. (15th July 2022) - Johnson, Corey M.; Fast, Walter
Graphical abstract: Abstract: Dimethylarginine dimethylaminohydrolase (DDAH, EC 3.5.3.18) catalyzes the hydrolysis of asymmetric N ω, N ω -dimethyl-l -arginine (ADMA), an endogenous inhibitor of human nitric oxide synthases. The active-site cysteine residue has been proposed to serve as the catalytic nucleophile, forming an S -alkylthiourea reaction intermediate, and serving as a target for covalent inhibitors. Inhibition can lead to ADMA accumulation and downstream inhibition of nitric oxide production. Prior studies have provided experimental evidence for formation of this covalent adduct but have not characterized it kinetically. Here, rapid quench-flow is used with ADMA and the DDAH from Pseudomonas aeruginosa to determine the rate constants for formation ( k 2 = 17 ± 2 s −1 ) and decay ( k 3 = 1.5 ± 0.1 s −1 ) of the covalent S -alkylthiourea adduct. A minimal kinetic mechanism for DDAH is proposed that supports the kinetic competence of this species as a covalent reaction intermediate and assigns the rate-limiting step in substrate turnover as hydrolysis of this intermediate. This work helps elucidate the different reactivities of S -alkylthiourea intermediates found among the mechanistically diverse pentein superfamily of guanidine-modifying enzymes and provides information useful for inhibitor development.